Effects of Rehabilitation on Perineural Nets and Synaptic Plasticity Following Spinal Cord Transection - Al’joboori, Yazi D. (Brain Sci, 2020)
Epidural electrical stimulation (ES) of the lumbar spinal cord combined with daily locomotor training has been demonstrated to enhance stepping ability after complete spinal transection in rodents and clinically complete spinal injuries in humans. Although functional gain is observed, plasticity mechanisms associated with such recovery remain mostly unclear. Here, we investigated how ES and locomotor training affected expression of chondroitin sulfate proteoglycans (CSPG), perineuronal nets (PNN), and synaptic plasticity on spinal motoneurons. To test this, adult rats received a complete spinal transection (T9–T10) followed by daily locomotor training performed under ES with administration of quipazine (a serotonin (5-HT) agonist) starting 7 days post-injury (dpi). Excitatory and inhibitory synaptic changes were examined at 7, 21, and 67 dpi in addition to PNN and CSPG expression. The total amount of CSPG expression significantly increased with time after injury, with no effect of training. An interesting finding was that γ-motoneurons did not express PNNs, whereas α-motoneurons demonstrated well-defined PNNs. This remarkable difference is reflected in the greater extent of synaptic changes observed in γ-motoneurons compared to α-motoneurons. A medium negative correlation between CSPG expression and changes in putative synapses around α-motoneurons was found, but no correlation was identified for γ-motoneurons. These results suggest that modulation of γ-motoneuron activity is an important mechanism associated with functional recovery induced by locomotor training under ES after a complete spinal transection.